FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT (Media Riset Akuntansi, 2022)
The purpose of this research is to test the locus of control, obedience pressure, task complexity, and auditor competency on audit judgment. The population in this research is the auditor of the Big Four Public Accountant firm at DKI Jakarta in 2020. Determination of the sample for initial participants in this research uses the probability sampling method that is using simple random sampling and then using snowball sampling techniques to meet the desired number of samples. Data collection techniques in this research used a questionnaires method and the sample has been obtained by 52 respondents. The analytical method used to test hypotheses is multiple linear regression. The results of this research prove that the obedience pressure and task complexity has effect on the audit judgment, while the locus of control and auditor competency has not effect on the audit judgment.